To Every Thing There Is a Season: Phenology and Photoperiodic Control of Seasonal Development in the Invasive Caucasian Population of the Brown Marmorated Stink Bug, Halyomorpha halys (Hemiptera: Heteroptera: Pentatomidae) - Sergey Ya. Reznik; Natalia N. Karpun; Vilena Ye. Zakharchenko; Yelena I. Shoshina; Margarita Yu. Dolgovskaya; Aida Kh. Saulich; Dmitry L. Musolin (Insects, 2022)
Studies on the phenology of local populations of invasive insects are necessary for monitoring and predicting their dispersion. We investigated the phenology of the brown marmorated stink bug, Halyomorpha halys, in the Sochi region (Krasnodar Territory, Russia) from 2018 to 2021 by regular field sampling and dissecting. The results of the sampling suggest that H. halys is at least partially bivoltine in the studied region: the main period of mass oviposition (by the overwintered females) occurs from June to July; the second, much shorter period of egg-laying (by females of the new, i.e., the first generation) occurs in August. Reproductively active individuals (i.e., females with developed ovaries and filled spermatheca and males with filled ectodermal sac) were recorded from the end of May to the beginning of September. Such a seasonal pattern correlated with day length: when the natural photoperiod decreased below the experimentally determined critical day length (15.0–15.5 h), the proportions of females with fully developed ovaries sharply dropped to zero. Both the rate of H. halys pre-adult development and the timing of the induction of winter adult diapause observed under natural conditions fully agreed with the earlier predictions that had been based on the results of laboratory experiments.